Traditional Surveys Versus Digital Surveys: Perspectives of Library and Information Science Researchers on Best Method for Data Collection in Research - Oladokun, Bolaji; Ajani, Yusuf; Tella, Adeyinka (Folia Toruniensia, 2025)
Aims: This study examined the preferences of Library and Information Science (LIS) researchers in Nigeria regarding traditional (paper-based) versus digital (online) survey methods for data collection in research. The primary aim was to assess the perceived advantages, drawbacks, contextual influences, and practical challenges associated with both survey methodologies. Method: A mixed-method research design was employed, involving quantitative data from structured questionnaires and qualitative insights from open-ended responses. The study utilized convenience sampling techniques, targeting LIS researchers across Nigerian universities through the NALISE WhatsApp platform. Data were collected via Google Forms and analyzed using descriptive statistics and thematic analysis. Results: Findings revealed a slight preference for digital surveys (53.2%) over traditional surveys (46.8%), largely due to the benefits such as time efficiency, cost-effectiveness, broader reach, and enhanced data analysis capabilities. However, traditional surveys were preferred for their data accuracy and ease of administration in low-tech contexts. Key factors influencing researchers’ preferences included researcher expertise, population characteristics, time constraints, and technological infrastructure. Major challenges identified were difficulties in ensuring data quality, limited access to technology, and insufficient training in survey design. Despite the promise of digital surveys, representativeness, technical issues, and ethical concerns persist. Conclusion: The studyconcluded that there is no one-size-fits-all approach to survey methodology. While digital tools offer significant operational advantages, they must be balanced against contextual limitations such as digital divides, technical capacity, and representativeness. Traditional methods retain value, especially where trust, accuracy, or accessibility is paramount. A hybrid or adaptive survey approach, supported by institutional training, technological investment, and ethical oversight, is recommended to optimize research effectiveness and inclusiveness in the Nigerian LIS context.